TOWARDS A NEW PHILOSOPHICAL IMAGINARY. Issue 1 (3rd March 2020) - Anderson, Pamela Sue; Lovibond, Sabina; Moore, A.W.
Abstract: The paper builds on the postulate of "myths we live by, " which shape our imaginative life (and hence our social expectations), but which are also open to reflective study and reinvention. It applies this principle, in particular, to the concepts of love and vulnerability. We are accustomed to think of the condition of vulnerability in an objectifying and distancing way, as something that affects the bearers of specific (disadvantaged) social identities. Against this picture, which can serve as a pretext for paternalist and controlling attitudes to the groups in question – notably to women – Anderson urges us to reimagine our vulnerability as a condition not merely of exposure to violence but of openness to mutual affection, love, and friendship. Hegel's celebrated image of the owl of Minerva, which takes wing only with the coming of dusk, suggests an association of (philosophical) wisdom with negativity – with the experience of death or loss. Anderson, by contrast, proposes an alternative and more hopeful image of the dawn of enlightenment, in the guise of new ethical dispositions shaped by an emancipatory (and so, no longer an oppressive or sexist) conception of our capacity for love. Her main interlocutors or influences in this piece are Judith Butler (who contributes the idea of a "relational ontology"), Michèle Le Doeuff, and Mary Midgley.